2016
DOI: 10.1074/jbc.m116.725937
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eicosanoids Produced by Adipocyte Lipolysis

Abstract: Excessive adipocyte lipolysis generates lipid mediators and triggers inflammation in adipose tissue. However, the specific roles of lipolysis-generated mediators in adipose inflammation remain to be elucidated. In the present study, cultured 3T3-L1 adipocytes were treated with isoproterenol to activate lipolysis and the fatty acyl lipidome of released lipids was determined by using LC-MS/MS. We observed that ␤-adrenergic activation elevated levels of approximately fifty lipid species, including metabolites of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…For example, adipocyte-specific Mcp-1 transgenic mice exhibit increased ATMs and whole-body insulin resistance (42). It has been demonstrated that several lipid metabolites released from adipocytes or adipose tissue participate in inflammatory cell activation (15,16,32,43,44). Eicosanoids produced from adipocytes promote recruitment of immune cells (16,32), whereas palmitoleate and palmitic acid-9-hydroxy stearic acid from adipose tissue reduce pro-inflammatory response in immune cells (15,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, adipocyte-specific Mcp-1 transgenic mice exhibit increased ATMs and whole-body insulin resistance (42). It has been demonstrated that several lipid metabolites released from adipocytes or adipose tissue participate in inflammatory cell activation (15,16,32,43,44). Eicosanoids produced from adipocytes promote recruitment of immune cells (16,32), whereas palmitoleate and palmitic acid-9-hydroxy stearic acid from adipose tissue reduce pro-inflammatory response in immune cells (15,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…nists or forskolin to stimulate lipolysis, lipid metabolites generated from COX are elevated (16,32). Administration of ␤ 3 -adrenergic agonist increases macrophage infiltration into WAT, which can be abrogated by COX2 inhibitor (16).…”
Section: Roles Of Plin1 In Adipose Tissue Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…The most abundant oxylipid substrates are linoleic (LA) and arachidonic (ArA) acids. Studies in rodent models of lipolysis demonstrate that the activation of cyclooxygenase 2 (COX2) and 5- and 15- lipoxygenases (5LOX, 15LOX) during lipolytic events enhances oxylipid biosynthesis [ 11 ]. LA-derived oxylipids, including 9- and 13-hydroxyl-octadecadienoic acids (HODE), promote inflammatory responses within AT by acting as chemoattractants of AT macrophages [ 12 ].…”
Section: Introductionmentioning
confidence: 99%